The Enhancement of Consistency of Interpretation Skills on the Newton’s Laws Concept - Yudi Kurniawan (JIPF (Jurnal Ilmu Pendidikan Fisika), 2018)
Conceptual understanding is the most important thing that students should have rather than they had reaches achievement. The interpretation skill is one of conceptual understanding aspects. The aim of this paper is to know the consistency of students’ interpreting skills and all at once to get the levels of increasing of students’ interpretations skill. These variables learned by Interactive Lecture Demonstrations (ILD) common sense. The method of this research is pre-experimental research with one group pretest-posttest design. The sample has taken by cluster random sampling. The result had shown that 16 % of all student that are have perfect consistency of interpretation skill and there are increasing of interpretation skill on 84 % from unknown to be understand (this skill). This finding could be used by the future researcher to study in the other areas of conceptual understanding aspects